Analisis Sistem Kompensasi (Studi Kasus PT XYZ) - Safira Hasan, Elsya; Christian Wiradendi Wolor; Marsofiyati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Companies must be able to create encouraging conditions and enable the development and improvements of existing abilities and skills to be done optimally. One way a company can accomplish this is by compensating all its employees. Compensation is everything that is given to employees as a settlement on their job. With good compensation, forms of payment, benefits, and incentives can motivate employees to increase their productivity at work and be done optimally. The study uses a qualitative descriptive approach that is to describe and analyze the problems found. Qualitative research is based on primary and secondary data. Primary data in this study is obtained by direct and indirect observation such as pre-research, interviews, and documentation, while secondary data is obtained through research-related books, previous studies, and articles. The purpose of this study is to know and explain the system of compensation used in PT XYZ includes direct compensation application and indirect compensation application. The results of this study may be known that PT XYZ has provided both immediate and indirect compensation and has applied indirect compensation, but it has not been given in time and employees have not received both direct and indirect compensation. That can be proved by interviews and research done.